Place of great extinctions in the new ecological paradigm - Кипоренко, О. Я.; Шабалтас, Г. Б.; Сокольський, Т. Г. (Proceedings of National Aviation University, 2013)
The paper demonstrates importance of the knowledge of the causes and consequences of the Great extinctions that occurred before the origin of man, in the formation of a new environmental paradigm. Were described methodological foundations of paleoecological studies. Were analyzed the fossilized remains found directly by the authors on the territory of Ukraine. In the development of new environmental paradigm is necessary to consider knowledge of the great extinction (the knowledge of the past), because it is an event, that can be used not only to study past, as well as predicting the same events in the future